Antimicrobial Activity of Manganese(I) Tricarbonyl Complexes Bearing 1,2,3-Triazole Ligands - Sofia Friães; Cândida Trigueiros; Clara S. B. Gomes; Alexandra R. Fernandes; Oscar A. Lenis-Rojas; Marta Martins; Beatriz Royo (Molecules, 2023)
Background. Antimicrobial resistance is one of the most pressing health issues of our time. The increase in the number of antibiotic-resistant bacteria allied to the lack of new antibiotics has contributed to the current crisis. It has been predicted that if this situation is not dealt with, we will be facing 10 million deaths due to multidrug resistant infections per year by 2050, surpassing cancer-related deaths. This alarming scenario has refocused attention into researching alternative drugs to treat multidrug-resistant infections. Aims. In this study, the antimicrobial activities of four manganese complexes containing 1,2,3,-triazole and clotrimazole ligands have been evaluated. It is known that azole antibiotics coordinated to manganese tricarbonyl complexes display interesting antimicrobial activities against several microbes. In this work, the effect of the introduction of 1,2,3,-triazole-derived ligands in the [Mn(CO)3(clotrimazole)] fragment has been investigated against one Gram-positive bacterium and five Gram-negative bacteria. Methods. The initial antimicrobial activity of the above-mentioned complexes was assessed by determining the minimum inhibitory and bactericidal concentrations using the broth microdilution method. Growth curves in the presence and absence of the complexes were performed to determine the effects of these complexes on the growth of the selected bacteria. A possible impact on cellular viability was determined by conducting the MTS assay on human monocytes. Results. Three of the Mn complexes investigated (4–6) had good antimicrobial activities against all the bacteria tested, with values ranging from 1.79 to 61.95 µM with minimal toxicity. Conclusions. Due to the increased problem of antibiotic resistance and a lack of new antibacterial drugs with no toxicity, these results are exciting and show that these types of complexes can be an avenue to pursue in the future.